1976
DOI: 10.1093/ajcn/29.10.1108
|View full text |Cite
|
Sign up to set email alerts
|

Calorigenic response in obese and nonobese women

Abstract: The calorigenic response to a high protein test meal was studied in women with a history of childhood onset obesity. Obese and nonobese individuals were fasted overnight and basal oxygen consumptions determined the following morning. A semisynthetic 823 kcal high protein test meal was ingested within a 1-hr period followed by hourly determinations of oxygen consumption and plasma levels of insulin, free fatty acids, triglycerides, glucose, amino acids, and urea nitrogen. Amino acid levels increased faster and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0
1

Year Published

1983
1983
2003
2003

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(28 citation statements)
references
References 15 publications
3
24
0
1
Order By: Relevance
“…Although the quantitative thermogenic effect of physiologically liberated norepinephrine is not known, it is possible that the observed rise in norepinephrine contributed to part of the unexplained rise (35- (6)(7)(8)(9) or diabetic obese subjects (10) (40) and possibly a greater absolute inhibition of gluconeogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the quantitative thermogenic effect of physiologically liberated norepinephrine is not known, it is possible that the observed rise in norepinephrine contributed to part of the unexplained rise (35- (6)(7)(8)(9) or diabetic obese subjects (10) (40) and possibly a greater absolute inhibition of gluconeogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a reduced thermic effect of a meal in obese subjects, in comparison with that of normal weight subjects, has been reported, (6)(7)(8)(9)(10). It has been postulated that this decreased dietary-induced thermogenesis might be involved in the etiology of obesity or the maintenance of the obese state.…”
Section: Introductionmentioning
confidence: 99%
“…The postprandial rise in caloric expenditure and its relationship to obesity have been the subject of intensive studies in the last decade. Numerous studies have shown that the thermic effect offood (TEF)' is blunted in obese subjects (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). The authors of these reports claimed that because fewer nutrients were oxidized by obese humans, relatively more nutrients were stored by obese than lean people per caloric intake.…”
Section: Introductionmentioning
confidence: 99%
“…Further, it should be possible to demonstrate that obese people have a reduced capacity for thermogenesis. Pittet et al (1976) found differences between lean and obese women in the size of response to a small meal (50 g glucose), but this was not confirmed by other workers (Kaplan & Leveille 1976, Clough & Durnin 1970. Blaza (1980) found no differences in the response of five lean and five obese women to a 1000 kcal (4.2 MJ) meal and moderate exercise although there were some differences in response to warm and cool environmental temperatures (all within 20-30"C and described by the subjects as 'comfortable').…”
Section: Adult Manmentioning
confidence: 75%